2016
DOI: 10.18632/oncotarget.13451
|View full text |Cite
|
Sign up to set email alerts
|

Common profiles of Notch signaling differentiate disease-free survival in luminal type A and triple negative breast cancer

Abstract: Breast cancer (BC) is characterized by high heterogeneity regarding its biology and clinical characteristics. The Notch pathway regulates such processes as organ modeling and epithelial-to-mesenchymal transition (EMT). The aim of the study was to determine the effect of differential expression of Notch members on disease-free survival (DFS) in luminal type A (lumA) and triple negative (TN) BC. The differential expression of 19 Notch members was examined in a TCGA BC cohort. DFS analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…Meanwhile, HES1 upregulation was correlated with lower PFS and OS in patients with TNBC. A recent study also revealed that HES1 upregulation predicts an unfavourable prognosis in TNBC 29 . To date, there is still no targeted and effective treatment strategy for TNBC due to deficiencies in therapeutic targets.…”
Section: Discussionmentioning
confidence: 92%
“…Meanwhile, HES1 upregulation was correlated with lower PFS and OS in patients with TNBC. A recent study also revealed that HES1 upregulation predicts an unfavourable prognosis in TNBC 29 . To date, there is still no targeted and effective treatment strategy for TNBC due to deficiencies in therapeutic targets.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, PRS was significantly better for patients with luminal breast cancer who achieved pCR, but not for those with TNBC. Luminal breast cancer comprises epithelial cells and has low invasion capability, whereas TNBC comprises mesenchymal cells, and has high invasion and migration capabilities [ 28 , 29 ]. Compared to that of the primary tumor, relapsed breast cancer after NAC and surgery often acquires resistance to chemotherapy; thus, the prognosis may depend on the degree of invasion or migration rather than immunoactivity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that PSEN1 was involved in the process of invasion and metastasis of gastric cancer both in vitro and vivo, 30 which may be regarded as a potential biomarker and therapeutic target. On the other hand, PSEN1 was also reported to be a tumour suppressor, and the enhanced expression of PSEN1 was associated with a favourable disease‐free survival for patients with breast cancer32 and skin cancer 33. However, little is known for its role in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%